MENGENALI KARAKTERISTIK ANAK BERKEBUTUHAN KHUSUS - Eka Damayanti Nasution; Yang Gusti Feriyanti; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
Educating children with special needs is a challenge in the world of education, because not all schools are ready to accommodate children with special needs in their educational environment. Children with special needs generally grow and develop with a number of differences compared to children in general. In special education in Indonesia, children with special needs are classified into blind, deaf, physically disabled, mentally retarded and hearing impaired. Every child with special needs also requires special services that are appropriate to their abilities and characteristics. It is important to carry out activities that recognize not only the abilities and needs of children with special needs, but also their characteristics. The aim of this research is to identify the characteristics of ABK. The methods used were observation, interviews and documentation, after which the data was analyzed qualitatively and descriptively. Social and communication development is the most important disorder, as in normal people, impaired verbal intelligence or language, and difficulty in continually renewing behavior, desires, pleasures and habits. Based on interviews, observations and literature, children with special needs are proven to have characteristics in the areas of communication, social interaction, sensory abilities, playing styles, behavior and emotions.